Internal Medicine Diagnosis and Therapy - Khan, M. G. M. Gabriel (Jaypee Brothers Medical Publishers, 2020)
The aim of this book is to focus on the diagnosis and therapy of internal medicine. The aim of this book is to provide internists, family physicians, general practitioners, and doctors in the field with an accurate and up-to-date source of easily retrievable information on how to diagnose and treat medical diseases and conditions frequently encountered in office practice. This book consists of 28 chapters, which include hypertension, angina, acute myocardial infarction, sitosterolemia, heart failure, arrhythmias, valvular heart disease, rheumatic fever, dyslipidemia and sitosterolemia, infective endocarditis, cardiomyopathy, syncope, pneumonias, gastrointestinal disease, liver disease, neurologic disorder, renal disease, hematologic disorder, rheumatic disorder, etc. Accurate diagnosis and relevant pathophysiology are essential to evolve adequate therapy, and in text, these areas are well covered. This is one of the first medium-sized books to cover all of internal medicine, giving practical straightforward advice. This comprehensive guide to the management of the most important diseases completely covers diagnosis and therapy in an easy-to-use format.